2016
DOI: 10.1111/deci.12198
|View full text |Cite
|
Sign up to set email alerts
|

Stockout Recovery under Consignment: The Role of Inventory Ownership in Supply Chains

Abstract: We examine how a supply chain firm may implement an incentive contract under inventory consignment to recover stockouts and to retain customers. Inventory consignment allows an upstream firm (e.g., a manufacturer) to own and control inventory at a downstream firm (e.g., a retailer), representing a structural change in supply chain governance. Motivated by cases in pet toy and electronics component industries, we formulate principal–agent models based on the newsvendor framework to capture the strategic interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…VMI was initiated as a promising collaborative approach to managing inventories of the buyer by its supplier (Waller et al , 1999; Yu et al , 2009; Yao et al , 2012; Xu et al , 2016). To date, extant literature includes several studies related to the factors that affect the successful implementation of VMI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…VMI was initiated as a promising collaborative approach to managing inventories of the buyer by its supplier (Waller et al , 1999; Yu et al , 2009; Yao et al , 2012; Xu et al , 2016). To date, extant literature includes several studies related to the factors that affect the successful implementation of VMI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A steady stream of studies on the importance of demand management and on the provision of strong linkage between demand and supply has been reported in the literature (Chuang and Oliva, 2015;Kosior and Strong, 2006;Holmström et al, 2010). However, most retailers and distributors struggle to have the right stock-keeping unit (SKU) at the right place, in the right quantity, and at the right time to meet the demands of their customers (Christopher and Ryals, 2014) with others such as Xu et al (2016), examining how to recover from getting these decisions wrong such as having stockouts and in turn how to retain customers in these circumstances. In response to increasingly shortening product-life-cycles, higher customer expectation, intense price competition and fierce global competition between retail chains, i.e., discount stores, supermarkets or convenient stores; it is imperative to understand the optimum service level needed to satisfy consumers (Elsayed, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supporting this view, reports from industry suggest significant positive benefits from implementing IC programs (Sullivan, 2008;and Valentini & Zavanella 2003). Recently, Xu et al (2016) found that IC programs can reduce the risk of stockouts, thus benefiting the focal firm. However, Rungtusanatham et al (2007) found that results obtained from utilizing IC in a retail setting are far from optimal due to increased information asymmetries and high monitoring costs for retailers.…”
Section: Introductionmentioning
confidence: 97%